Correcting spelling errors by modelling their causes - Deorowicz, Sebastian; Ciura, Marcin G. (Zielona Góra: Uniwersytet Zielonogórski)
This paper accounts for a new technique of correcting isolated words in typed texts. A language-dependent set of string substitutions reflects the surface form of errors that result from vocabulary incompetence, misspellings, or mistypings. Candidate corrections are formed by applying the substitutions to text words absent from the computer lexicon.
Keywords: spelling correction; finite state automata; spelling errors